Optimalisasi patroli roda dua Satuan Sabhara Polres Kab Tasikmalaya dalam mencegah tindak pidana pencurian kendaraan bermotor - Bachdar, Yofan Pratama (Advances in Police Science Research Journal, 2019)
The focus of this thesis research is about Optimizing two-wheeled patrol Sabhara Unit of Tasikmalaya District Police in preventing motor theft. The focus of this study is seen as important considering the high crime of motor vehicle theft that occurred in Tasikmalaya District, so that the implementation of two-wheeled patrol activities owned by Sabhara Unit can prevent the occurrence of motorized theft if it is optimally carried out. There are three issues raised in this thesis research, namely about: (1) How is the implementation of two-wheeled patrol in preventing the theft of motorized vehicles in the legal area of ​​the Tasikmalaya District Police? (2) What are the factors that cause motor vehicle theft in the legal area of ​​the Tasikmalaya District Police? (3) What is the effort to optimize wheel patrol to prevent theft of motorized vehicles? To analyze these three problems, the author uses the Research field method with a qualitative approach, the use of a conceptual framework in the form of theory and concepts used as a knife of analysis by the author in answering the formulated problem. Theories and concepts used by the author are management theory, swot analysis theory and optimization concepts. The findings of this study are (1) Lack of number and ability of Sabhara unit two-wheeled patrol members, (2) What hinders the implementation of two-wheeled patrol in preventing motor theft due to internal and external factors so that the ability of members in the field of knowledge, and skills must be (3) Lack of synergy between Sabhara units and other units in the implementation of two-wheeled patrols. From these research findings, it is suggested that the Chief of Tasikmalaya District Police work together with the West Java Regional Police HR Bureau to increase the shortage of members and also provide innovation using technology in the implementation of patrol. Keywords: Two Wheel Patrol, Preventing, Motorized Theft Crime, Tasikmalaya District Police